PENGARUH VIDEO TUTORIAL GARDAN (DIFFERENTIAL) TERHADAP HASIL BELAJAR PADA MATA KULIAH SISTEM PEMINDAHAN TENAGA - Muhammad Rifki Firdaus; Iffarial Nanda; Wakhinuddin Simatupang; Rifdarmon Rifdarmon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The advancement of technology demands learning media that are more engaging and interactive. In the Power Transmission Systems course, instruction is still dominated by lectures, resulting in suboptimal student comprehension. This study aims to examine the effectiveness of a differential tutorial video as a learning medium. The research employed a pre-experimental one-group pretest–posttest design involving 30 Automotive Engineering students. A test instrument was administered before and after the intervention. Normality tests showed that pretest data were normally distributed, while posttest data were not, leading to the use of the Wilcoxon Signed Rank test. The results indicated an improvement in learning outcomes, with 30 positive ranks. A Z-value of –4.798 and p = 0.000 confirmed a significant difference. The effect size of 0.876 indicated a very strong impact. Overall, the tutorial video proved effective in enhancing students’ understanding of differential concepts through visual and auditory stimulation.Keywords: Video Tutorial, Differential, Learning Outcomes, Learning Media, Power Transmission System